STRATEGY TO INCREASE THE EXISTENCE OF WAQF FEATURES IN ALLISYA PROTECTION PLUS PRODUCTS - Siregar, Pratista Andanitya; Imsar, Imsar (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2022)
The waqf feature in insurance products in Indonesia has the potential to grow along with the large role of waqf in improving the welfare of the people. This study aims to analyze strategies that can be used to improve the existence of waqf features in allisya protection plus products. This research uses qualitative descriptive methods, namely research that explains data and information based on facts obtained in the field. Based on the results of research and discussion, the marketing concept carried out includes products, prices, places and promotions. The marketing strategy is also through an agent and who understands the concept of sales to convince potential customers. An agent in carrying out his duties and obligations must adhere to the code of ethics and act as a good advisor, have insight, knowledge of sharia insurance products, have morals, manners, care and easy to get along with. The attitude of an agent is an important capital so that people can easily understand the products and services of sharia insurance. The company also cooperates with several waqf institutions. Keywords: Waqf Feature, Allisya Protection Plus, Strategy